Overcoming extinction: understanding processes of recovery of the Tibetan antelope. Issue 9 (30th September 2015) - Leclerc, C.; Bellard, C.; Luque, G. M.; Courchamp, F.
Abstract : Since the middle of the 20th century, the Tibetan antelope ( Pantholops hodgsonii ) has been poached for its wool to make luxury shawls, shahtoosh . This direct overexploitation caused a drastic decline in their population, with a loss of more than 90% compared to the baseline population a few decades ago. Assuming this is an anthropogenic Allee effect (AAE), human attraction for rarity can drive rare species to extinction, which could explain the increasing rates of antelope harvests, paralleling the escalating prices of shahtoosh as the species got rarer. Since 1999, international concern led to conservation actions and the population soon started increasing. This unique situation allowed the presence of an AAE in Tibetan antelope to be tested, as well as an assessment of the potential effects of conservation actions in the presence of this process. We developed a theoretical discrete‐time population dynamics model and examined effects of variation in shahtoosh prices. Furthermore, we tested the effects of major conservation actions into our models assessing their relative contribution to population recovery. During the exploitation phase, we found some evidence supporting the presence of an AAE compared to non‐AAE models when hunting ceased at antelope population sizes below 10% of the initial population size. Regarding the conservation phase, our results suggested that poacher numbers reduction had the most likely positive impact on Tibetan antelope population dynamics. As many other species are similarly declining and/or close to extinction, our results suggest that adequate conservation actions could counter the most dramatic declines, even when populations have entered an extinction vortex.